Big Data Analytics and Business Intelligence in Business Marketing: A Review - Duong, Vacharasip (International Journal of Information Technology and Computer Science Applications, 2024)
The aim of this paper is to conduct an extensive study on big data analytics and business intelligence (BI) in marketing that is within the academic research sphere. Research gaps were identified and development for future research on the study was highlighted. A systematic review based on literature which related academic articles indexed in Web of Science and Scopus databases was used. The articles reviewed were based on certain features like theoretical and conceptual characterization; data source; research topic; type and size of data; data analysis techniques and methods used in data collection. The research outcome indicates that there is an increase in the marketing research with analytical technique applies to large quantity of data. However, this research area is limited in scope and methodologies and presents several gaps. A conceptual framework that will help in detecting important business challenges and relate the domain of big data and business intelligence to marketing is missing. This study contributes to exploring systematically the awareness of marketers working in big data and business intelligence.